Pengaruh Brand Image terhadap Brand Loyalty dengan Satisfaction dan Brand Trust sebagai Variabel Mediasi (Studi Kasus pada Smartphone Merek Xiaomi di Yogyakarta) - Reza, Ceva Faza; Nyoman Udayana, Ida Bagus; Kusuma Ningrum, Nonik (Universitas Hamzanwadi, 2024)
The rapid growth of the Smartphone industry. Xiaomi, which is a smartphone manufacturer, experienced a decline in sales from Q3 2022 to Q1 2023. So researchers intend to test the influence of brand image, satisfaction and brand trust on brand loyalty on Xiaomi brand smartphones in Yogyakarta. This research uses a descriptive quantitative approach. There was a sample of 160 respondents, using structural equation model (SEM) data analysis techniques with partial least squares (PLS) statistical tools. It was found that the test results showed that brand image has a positive and significant impact on brand loyalty. Brand image has a positive and significant impact on satisfaction. Brand image has a positive and significant impact on brand trust. Satisfaction has a positive and significant impact on brand loyalty. Brand trust has a positive and significant impact on brand loyalty. Satisfaction cannot mediate between brand image and brand loyalty. However, brand trust can mediate between brand image and brand loyalty.